2019
DOI: 10.1186/s13014-019-1402-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the optimal re-irradiation dose for locally recurrent esophageal squamous cell carcinoma after definitive radiotherapy

Abstract: BackgroundRe-irradiation (re-RT) has the active effect of relieving clinical symptoms and prolonging the survival of patients with recurrent esophageal squamous cell carcinoma (ESCC). However, the optimal re-RT dose is still uncertain. Here, we analyzed the prognostic factors associated with survival and explored the optimal re-RT dose for patients with recurrent ESCC following definitive radiotherapy.Patients and methodsThe data of 47 patients with recurrent ESCC who were retreated between 2010 and 2014 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 21 publications
6
22
1
Order By: Relevance
“…The 5-years OS rate was 32.1% in salvage radiotherapy patients, and the median survival time was 39.0 months, which is longer than those reported in other studies [ 13 , 14 ]. The median ARS was 13.0 months (range 3–168 months), which was similar to the results of previous studies [ 12 17 , 29 ]. Therefore, further research is needed to improve the survival time after recurrence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The 5-years OS rate was 32.1% in salvage radiotherapy patients, and the median survival time was 39.0 months, which is longer than those reported in other studies [ 13 , 14 ]. The median ARS was 13.0 months (range 3–168 months), which was similar to the results of previous studies [ 12 17 , 29 ]. Therefore, further research is needed to improve the survival time after recurrence.…”
Section: Discussionsupporting
confidence: 90%
“…Re-irradiation has been successfully used in many recurrent tumors of various sites with the development of radiotherapy techniques, such as head and neck cancer [ 7 , 22 ], high grade glioma [ 23 ], lung cancer [ 24 ], intracranial germ-cell tumors [ 25 ], rectal cancer [ 26 , 27 ] and paediatric tumor [ 28 ] with encouraging results. Several small size retrospective studies reported the outcome of re-RT of LR for ESCC patients received RT [ 14 , 17 , 29 ]. The only prospective study reported that re-RT for oligo-recurrence in lymph nodes from esophageal cancer treated by definitive RT or by surgery with additional RT might be acceptable but unsatisfactory [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 5-years OS rate was 32.1% in salvage radiotherapy patients, and the median survival time was 39.0 months, which is longer than those reported in other studies [12,13]. The median ARS was 13.0 months (range 3-168 months), which was similar to the results of previous studies [11][12][13][14][15]26]. Therefore, further research is needed to improve the survival time after recurrence.…”
Section: Discussionsupporting
confidence: 78%
“…Re-irradiation has been successfully used in many recurrent tumors of various sites with the development of radiotherapy techniques, such as head and neck cancer [7,19], high grade glioma [20], lung cancer [21], intracranial germ-cell tumors [22], rectal cancer [23,24] and paediatric tumor [25] with encouraging results. Several small size studies reported the outcome of re-RT of LR for ESCC patients received RT [13,15,26]. In our present study, we found that there was a signi cant increase in OS for patients who received re-RT.…”
Section: Discussionsupporting
confidence: 63%
“…To date, the aging of population has been progressing and elderly patients with esophageal cancer are more likely to be treated with CRT or RT alone, instead of surgery, for comorbidities and treatment risks [29,30]. Salvage PDT is reported to be a safer and more effective treatment option than other minimally invasive treatments such as re-irradiation or endoluminal brachytherapy in elderly patients [31,32]. Finally, we hope that salvage PDT using talaporfin sodium will be recognized as a promising salvage treatment for esophageal cancer with local failure after CRT and function as a treatment of choice in the future.…”
Section: Discussionmentioning
confidence: 99%